2010
DOI: 10.1371/journal.ppat.1001229
|View full text |Cite
|
Sign up to set email alerts
|

Glacial Refugia in Pathogens: European Genetic Structure of Anther Smut Pathogens on Silene latifolia and Silene dioica

Abstract: Climate warming is predicted to increase the frequency of invasions by pathogens and to cause the large-scale redistribution of native host species, with dramatic consequences on the health of domesticated and wild populations of plants and animals. The study of historic range shifts in response to climate change, such as during interglacial cycles, can help in the prediction of the routes and dynamics of infectious diseases during the impending ecosystem changes. Here we studied the population structure in Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(127 citation statements)
references
References 119 publications
(139 reference statements)
7
120
0
Order By: Relevance
“…Surprisingly, however, the degree of syngamy compatibility did not continue to decrease at larger genetic distances, remaining quite high. That inhibition of interspecific gamete fusion does not further decrease at higher genetic distance is intriguing given the evolution of postsyngamy isolation, with continual increase of hybrid inviability and sterility at these genetic distances, and the overlapping ranges of the species (Bucheli et al, 2000;Le Gac et al, 2007a, b;Hood et al, 2010;Gladieux et al, 2010b;Vercken et al, 2010). One may think that reinforcement would have kept on occurring to avoid producing unfit hybrids, especially at the greatest genetic distances where postsyngamy isolation is the strongest.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, however, the degree of syngamy compatibility did not continue to decrease at larger genetic distances, remaining quite high. That inhibition of interspecific gamete fusion does not further decrease at higher genetic distance is intriguing given the evolution of postsyngamy isolation, with continual increase of hybrid inviability and sterility at these genetic distances, and the overlapping ranges of the species (Bucheli et al, 2000;Le Gac et al, 2007a, b;Hood et al, 2010;Gladieux et al, 2010b;Vercken et al, 2010). One may think that reinforcement would have kept on occurring to avoid producing unfit hybrids, especially at the greatest genetic distances where postsyngamy isolation is the strongest.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the first scenario, it is now well documented that several European plant species are strongly structured genetically by previous occupancy in different glacial refugias (Hewitt 2000; for a recent review, see Vercken et al 2010). Several refugia have been identified, notably in Iberia, Italy, and the Balkans, and others have been suggested in the northern and eastern part of Europe (Bhagwat and Willis 2008;Stewart et al 2010).…”
Section: Introductionmentioning
confidence: 94%
“…Glaciation has had strong impacts on the biogeography and genetic diversity of a range of terrestrial species (Conroy and Cook, 2000;Milá et al, 2006;Wilson and Eigenmann Veraguth, 2010;Pointing et al, 2014;Newman and Austin, 2015) and has been shown to impact microbial diversity in soil (Vercken et al, 2010;Boyd et al, 2011;Park et al, 2011;Eisenlord et al, 2012;Stibal et al, 2012;Hamilton et al, 2013). Rapid demographic expansion resulting from glacial retreat has had profound impacts on the genetics of species (Hewitt, 1996;Conroy and Cook, 2000;Hewitt, 2000Hewitt, , 2004Wilson and Eigenmann Veraguth, 2010).…”
Section: Contributions Of Geography To Recombinationmentioning
confidence: 99%